Nawruz Celebrations in Ancient Mesopotamia - Akkuş Mutlu, Suzan (Archivum Anatolicum-Anadolu Arşivleri, 2016)
Ancient Mesopotamians were holding many ceremoniesdepending on their beliefs. Among these ceremonies, marriageceremony of Love Goddess Inanna and Shepherd God Dumuzi wasvery important. From myth describing marriage of Love GoddessInanna and Shepherd God Dumuzi, we learn how these ceremoniesthat were celebrated before Sumerians according to archaeologicalfindings, were started to be celebrated. It is understood from thesewritten documents that Mesopotamians identified God Dumuzi’sgoing underground with arrival of autumn, his meeting with Inannaby coming earth with arrival of spring. As a requirement of this belief,arrival of spring was celebrated with representative portrayal of thisholy marriage ceremony by king and mother superior in that timeevery year. This period was also regarded as the beginning of the newyear.Holy marriage ceremony, in other words, New Yearceremony was adopted by the Semitic tribes coming to Mesopotamiaafter Sumerians. Eski Mezopotamyalılar inançlarınabağlı olarak pek çok tören düzenliyorlardı. Bu törenler içerisinde AşkTanrıçası İnanna ile Çoban Tanrısı Dumuzi’nin evlenme töreni oldukça önemliydi.Arkeolojik bulgulardan, Sumerlilerden önce de kutlandığı anlaşılan butörenlerin, nasıl başladığını Aşk Tanrıçası İnanna ile Çoban Tanrısı Dumuzi’ninevliliğini anlatan bir mitostan öğrenmekteyiz. Yazılı belgelerden Mezopotamyalılarıntanrı Dumuzi’nin yer altına inişini, sonbaharın gelişi, yeryüzüne çıkıp İnannaile buluşmasını ise baharın gelişi ile özdeşleştirdikleri anlaşılmaktadır. Buinancın gereği olarak da her yıl, dönemin kralı ve baş rahibesi tarafından kutsalevlilik töreni, temsili bir şekilde canlandırılarak baharın gelişikutlanmıştır. Bu dönem aynı zamanda yeni bir yılın başlangıcı olarak kabuledilmiştir. Kutsal evlilik töreni, bir başka ifade ile Yeni Yıl TöreniSumerlilerden sonra Mezopotamya bölgesine gelen Sami kavimleri tarafından dabenimsenmiştir.